SLM of TI-6AL-4V single melt-tracks under different layer thickness and surface roughness - Tey, Cher Fu (2018)
The smallest feature that can be built using the selective laser melting (SLM) process is limited by the width of a single melt-track which can be minimized by lowering the laser energy input. However, melt-tracks could become unstable under low energy input due to insufficient melt pool penetration into the underlying layer. In this study, Ti-6Al-4V single melttracks are deposited using 3 different laser energy inputs (343, 240, 133J/m) on selected build layers starting from the sandblasted substrate on layer 1, to layer 45. The layer thickness and surface roughness (Pq) of the underlying layer progressively increase from 12±10μm to 46±24μm and 4.3±0.1μm to 25±6 μm respectively across the initial build layers. The width and continuity of the melt-tracks are measured across those layers and it is found that the track width increases with laser energy input but is not sensitive to layer thickness and the surface roughness of the underlying layer. The single melt-tracks processed with a 343J/m energy input remains continuous throughout all 45 build layers due to sufficient melt pool penetration into the underlying layer. The single melt-tracks processed under the 240J/m energy input is continuous from layers 1-7 but breaks up into discontinuous tracks from layer 9 onward when the layer thickness and surface roughness (Pq) exceeds 42±17μm and 17±2μm respectively. The single melt-tracks processed under 133J/m energy input is continuous on layer 1, discontinuous from layers 3-5, and undergoes complete “balling” from layer 7 onward where the layer thickness and surface roughness (Pq) exceeds 36±17μm and 18±2μm respectively. It is shown that the smallest printable feature, which corresponds to the width of a single melt-track, is mainly affected by the laser energy input while the continuity of such melt-tracks is maintained by limiting the layer thickness and surface roughness to sufficiently small values.